Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4102/sajip.v39i1.1109
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between emotional intelligence and leadership styles in the South African petrochemical industry

Abstract: Orientation: Although research on emotional intelligence in the context of leadership has remained a recurrent area of interest in theory and practice during the past decade, ongoing debate continues regarding the contribution of emotional intelligence to the understanding of leadership.Research purpose: The aim of this study was to determine the relationship between self-reported emotional intelligence and leadership styles in a South African context and to determine whether emotional intelligence can predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
1
11
0
2
Order By: Relevance
“…Similar reliabilities were reported by Ackermann, Scheepers, Lessing and Dannhauser (2000, cited Pillay et al (2013) found reliabilities between 0.61 and 0.93 in their study.…”
Section: Multifactor Leadership Questionnaire (Mlq 5x)supporting
confidence: 89%
See 1 more Smart Citation
“…Similar reliabilities were reported by Ackermann, Scheepers, Lessing and Dannhauser (2000, cited Pillay et al (2013) found reliabilities between 0.61 and 0.93 in their study.…”
Section: Multifactor Leadership Questionnaire (Mlq 5x)supporting
confidence: 89%
“…These studies provide empirical justification for the relationship between emotional intelligence and effective leadership. In a recent research study in a South-African petrochemical organisation, Pillay, Viviers and Mayer (2013) found significant positive relationships between emotional intelligence and transformational leadership.…”
Section: The Role Of Emotional Intelligence In Effective Leadershipmentioning
confidence: 93%
“…The focus though remains on customisation for the individual manager-leader's competencies. This focus on leader competencies and styles can be noted in research undertaken with South African samples as well (Baicher, 2005;Botha & Classens, 2010;Pillay, Viviers, & Mayer, 2013). Although the authors variously point out the need to broaden perspective and critically explore the South African context, the focus remains on individual leader competencies and styles.…”
Section: Contextualisation and Customisation (Demand-side Dynamics)mentioning
confidence: 98%
“…Today women occupy management and executive positions in any given social setup as Kinnear, (2014) and Mostert, (2009) contended. In this respect, du Toit et al (2017); Pillay et al (2013); Cavazotte et al (2012), stated that EI plays a significant role in the life of working females. Emotional Intelligence has considerably enhanced the success level of women leaders and workers on the job place (Jonck & Swanepoel, 2015).…”
Section: Introductionmentioning
confidence: 99%